Functional soil organic matter fractions in response to long-term fertilization in upland and paddy systems in South China - Yang, Fan; Tian, Jing; Meersmans, Jeroen; Fang, Huajun; Yang, Hao; Lou, Yilai; Li, Zhongfang; Liu, Kailou; Zhou, Yi; Blagodatskaya, Evgenia; Kuzyakov, Yakov (Elsevier, 2017)
Soil organic matter (SOM) and its fractions play key roles in optimizing crop yield and improving soil quality. However, how functional SOM fractions responded to long-term fertilization and their relative importance for C sequestration were less addressed. In this study, we determined the effects of long-term fertilization on six functional SOM fractions (unprotected, physically protected, physico-biochemically protected, physico-chemically protected, chemically protected, and biochemically protected) based on two long-term fertilization experiments carried out in South China. The unprotected coarse particulate organic matter (cPOM), the biochemically and chemically protected silt-sized fractions (NH-dSilt and H-dSilt) were the primary C storage fractions under long-term fertilization, accounting for 23.6–46.2%, 15.7–19.4%, and 14.4–17.4% of the total soil organic carbon (SOC) content in upland soil and 19.5–29.3%, 9.9–15.5%, and 14.2–17.2% of the total SOC content in paddy soil, respectively. Compared with the control treatment (CK) in upland soil, the application of manure combined with mineral NPK (NPKM) resulted in an increase in the SOC content in the cPOM, pure physically protected fraction (iPOM), the physico-chemically protected (H-μSilt), and the chemically protected (H-dSilt) fraction by 233%, 166%, 124%, and 58%, respectively. Besides, the SOC increase in upland soil expressed as SOC content per unit of total SOC for iPOM, H-μSilt, cPOM and H-dSilt were the highest and as large as 283%, 248%, 194%, and 105% respectively. In paddy soil, the highest increase per unit of total SOC was H-dSilt (190%), followed by H-dClay (156%) and H-μSilt (155%). These results suggested that the upland soil could stabilize more C through the pure physical, whereas the chemical protection mechanism played a more important role in paddy soil. Chemical protection mechanism within the microaggregates played important roles in sequestrating C in both upland and paddy soils. Overall, the different responses of functional SOM fractions to long-term fertilization indicate different mechanisms for SOM cycling in terms of C sequestration under upland and paddy systems.
Keywords: Long-term fertilization; Soil organic matter fraction; Physical and chemical fractionation; Protection mechanism